Physical and Dosimetric Characterization of Silicone Rubber Bolus for Head Photon-Beam Radiotherapy - Xuemei Chen MS; Wei Wang MS; Xiaotong Huang BS; Wenchao Diao BS; Chendi Xu MS; Lecheng Jia PHD; Hua Li PHD; Bin Li PHD; Xiaobo Jiang BS (Technology in Cancer Research & Treatment)
Objective This study assesses the physical properties of the silicone rubber (SR) bolus, compares its dosimetric characterization with those of gel and thermoset boluses, aiming to evaluate the feasibility and stability of utilizing SR bolus for head photon-beam radiotherapy. Methods Three types of boluses (gel, thermoset, and SR) were prepared with same dimensions. Firstly, the physical properties of SR bolus (density, tensile strength and hardness) were assessed pre-irradiation and post-irradiation. Secondly, the percentage of depth dose (PDD) curve was calculated using the treatment planning system (TPS) and measured with a plane-parallel. Thirdly, these three boluses were individually placed on the head phantom, followed by computed tomography (CT) scans to delineate the customized target area and organs at risk (OARs) for treatment planning. Over the subsequent three weeks, fan-beam CT (FBCT) images were obtained weekly and registered with the initial CT to modify the target area and OARs. Fourthly, the adhesion differences, dose distributions, and inter-fraction reproducibility of the three boluses were compared and evaluated. Results The results observed that post-irradiated SR bolus exhibited higher hardness values ( p  < .01) than the pre-irradiated one, with no significant differences in tensile strength and density. The PDD curves of all three boluses showed similarity within a difference range less than ±1%. The air gaps between the SR, thermoset, and gel boluses and skin surfaces were measured as 0.07 cm 3 , 2.96 cm 3 , and 4.82 cm 3 , respectively. Compared with gel bolus and thermoset bolus, the SR bolus demonstrated noticeable inter-fraction reproducibility. Conclusion The SR bolus can be fabricated at room temperature, adheres to irregular body surfaces, and retains its physical properties post-irradiation. Additionally, this bolus has comparable dosimetric characterization to other commercial boluses, and may provide notable protection for OARs. Therefore, the SR bolus is recommended as a feasible and stable material for head photon-beam radiotherapy.